Anemia in Pregnant Women and Its Determinants: A Cross-Sectional Study at Ummu Hani Mother and Children's Hospital, Purbalingga Regency - Fitriyani, Novita Endang; Amalia, Ary Nahdiyani; Jayanti, Rosita Dwi; Febriyanti, Rizka; Maryati, Leni (Jurusan Kesehatan Masyarakat dan Fakultas Ilmu-Ilmu Kesehatan Universitas Jenderal Soedirman, 2024)
Anemia in pregnant women is still a global problem, almost half of all pregnant women throughout the world experience anemia. Ummi Hani Mother and Children Hospital is one of the referral hospitals for mothers and children in Purbalingga that provides the antenatal care service. This research aimed to identify the determinants of anemia in pregnant women at Ummi Hani Mother and Children Hospital, Purbalingga. This research was an analytical observational study with a cross-sectional design. The total sample was 100 pregnant women. Data sources were obtained from medical records, parturition registers, and cohorts of pregnant women at Ummi Hani Mother and Children Hospital. Primary data collection used a structured questionnaire. Bivariate analysis used chi square and/or Fisher exact, and multivariate analysis used logistic regression. This research found that 51% of pregnant women suffered from anemia. The results of multivariate analysis showed that educational level (p value=0.002; OR=5.07; 95% CI=1.79-14.37) and employment status (p value=0.045; OR=2.73; 95% CI=1.02-7.29) were determinants of anemia in pregnant women. This research highlights importance of improving health promotion regarding dangers of anemia and prevention measures such as consuming nutritious and varied foods at affordable prices which is focused on groups of low-educated and unemployed pregnant women.